Pengaruh Promosi Islami dan Kualitas Pelayanan Islami terhadap Minat Nasabah pada Produk Cicil Emas - Ula, Zahrotul; Susilo, Edi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study examines the extent to which Islamic promotion and Islamic service quality affect customer interest in Cicil Emas products at Bank Syariah Indonesia KCP Jepara. The research was conducted with a quantitative approach, using 100 respondents selected through purposive sampling technique based on several criteria, namely BSI KCP Jepara customers who know the Cicil Emas product, have never used it, live in Jepara, and are 21-60 years old. Data was obtained through online questionnaire distribution and analyzed using multiple linear regression with the help of SPSS Statistics 22 software. The findings show that both independent variables have a significant influence on customer interest. Among them, Islamic service quality has the dominant influence with a regression coefficient of 0.464, followed by Islamic promotion at 0.357. The model is able to explain 50.9% of the variation in customer interest in the product, while the remaining 49.1% is influenced by other factors outside this study.